Design of a Consumer Complaint System at PT. Ampalu Indah Pratama Ekspres - Muhammad Sahroni; Sharyanto; Alexius Ulan Bani (Journal of Engineering, Technology and Computing (JETCom), 2022)
A complaint is defined as something that is unpleasant or something that is disturbing. Complaint behavior of the whistleblower is a very important phenomenon that must be understood by the owner of the company because the impact is directly related to the whistleblower. Complaints from Whistleblowers are not always negative because complaints from Whistleblowers are a form of their concern for the company's products or services. Whistleblowers who make complaints do not mean that they do not like the company's products and services, but it could be because they really like the company's services so that they hope that with the complaint the company's products and services can be of higher quality. From this problem, a UML (Unified Modeling Language) diagram is made which describes the interaction relationship between the system and the actor. Use Case can describe the type of interaction between the user of the system and the system. The method used in designing this information system is MySQL, and the application that supports the need to find a customer data.